2014
DOI: 10.1136/gutjnl-2013-306373
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin induces ductular reaction contributing to liver fibrosis

Abstract: OPN emerges as a key matricellular protein driving DR and contributing to scarring and liver fibrosis via TGF-β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 46 publications
13
106
0
1
Order By: Relevance
“…Indeed, TGF-βs impair hepatocyte lineage differentiation, promote cholangiocyte lineage differentiation (42,46), and increase EMT (30). Because SPP1 (osteopontin) produced by cholangiocytes also drives inflammatory cell infiltration, fibrosis, and cholangiocyte differentiation (47), some Mob1a/1b-deficient liver phenotypes may depend in part on SPP1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TGF-βs impair hepatocyte lineage differentiation, promote cholangiocyte lineage differentiation (42,46), and increase EMT (30). Because SPP1 (osteopontin) produced by cholangiocytes also drives inflammatory cell infiltration, fibrosis, and cholangiocyte differentiation (47), some Mob1a/1b-deficient liver phenotypes may depend in part on SPP1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (26) identified a role of OPN in HPC activation, and demonstrated that HPC-driven ductular reaction was a critical mechanism underlying the progression of liver fibrosis. Another study demonstrated that OPN neutralization suppressed liver fibrosis in mice (27).…”
Section: Discussionmentioning
confidence: 99%
“…Local expertise and personal experience with the model is likely to be an important factor when planning an experiment with TAA. Here we present our experience with the TAA model, which includes chronic oral exposure in C57BL/6 mice at a fixed dose (300 mg/L in drinking water) for 2-4 months, 13 IP injection of TAA in Sprague-Dawley rats for 11 weeks with or without an experimental drug, 14 and a time-course pilot study of TAA by IP injection in Sprague-Dawley rats for 12 weeks (Figure 1). We report the rate and degree of fibrosis and cirrhosis development, changes in portal pressures and liver collagen content, as well as the mortality rate in the experimental animals.…”
Section: Historical Background and Current Usagementioning
confidence: 99%
“…Our experience with orally administered TAA was recently published 13 and is summarized below as a standard for reference:…”
Section: Taa Via Oral Administrationmentioning
confidence: 99%